(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In this article, the average analysis of the laboratory-biochemical analyzes of the disease course in children with chronic viral hepatitis V and the development of the complications of acute otitis media developed against the background of SVGV are highlighted. Changes in the functional state of the middle ear are more evident when acute otitis media in children occurs against the background of chronic viral hepatitis В. When acute otitis media in children developed against the background of chronic viral hepatitis В, the clinical course of acute otitis media was specific, significantly severe and prolonged. According to the results of biochemical analyzes in the blood of sick children, it was found that as the activity of ALT increased, the clinical signs of acute otitis media in sick children also increased.